Formal variability in fishtail projectile points of Amigo Oeste archaeological site, Somuncurá plateau (Río Negro, Argentina) - Hermo, Darío (2012)
Fil: Hermo, Darío. División Arqueología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina